2010
DOI: 10.1016/j.hrthm.2010.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Rate-dependent action potential alternans in human heart failure implicates abnormal intracellular calcium handling

Abstract: Background-Alternans in action potential voltage (APV-ALT) at heart rates <110 beats/min is a novel index to predict ventricular arrhythmias. However, the rate-dependency of APV-ALT and its mechanisms in failing versus non-failing human myocardium are poorly understood. It is hypothesized that APV-ALT in human heart failure (HF) reflects abnormal calcium handling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 38 publications
(47 reference statements)
5
58
1
Order By: Relevance
“…Computational models of the LV wall in combination with clinical data revealed that abnormal handing of intracellular calcium underlies alternans in action potential voltage (APV-ALT), defined as the oscillation of the plateau voltage of the action potential, which results in MTWA at moderate heart rates, i.e. < 110 bpm (Bayer et al, 2010; Narayan et al, 2008). Thus APV-ALT is the cell-level driver of MTWA at these rates under the conditions of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Computational models of the LV wall in combination with clinical data revealed that abnormal handing of intracellular calcium underlies alternans in action potential voltage (APV-ALT), defined as the oscillation of the plateau voltage of the action potential, which results in MTWA at moderate heart rates, i.e. < 110 bpm (Bayer et al, 2010; Narayan et al, 2008). Thus APV-ALT is the cell-level driver of MTWA at these rates under the conditions of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…The slope of the APD restitution curve is determined by the recovery of ion channels from inactivation and their dependence on V m . Computational [21,25,26,28,29] as well as several experimental studies [30,31] have suggested that self-sustaining oscillations of APD can occur if this relationship is steep enough, and that the role of V m as a causative factor of alternans becomes more prominent with increasing pacing rates [28,32]. However, simulation results still differ and remain dependent on the computational models applied, even if they are designed to recreate processes of the same tissue [33].…”
Section: Putative Mechanisms Of Alternansmentioning
confidence: 99%
“…As discussed above disturbances in intracellular Ca 2+ handling have been proposed as an underlying mechanism of alternans at the cellular level [17,32,50,51,53,54,75]. Spatial heterogeneities in electrical as well as Ca 2+ cycling properties of cardiac tissue between the endocardium and epicardium or between the base and apex of the heart are essential for maintaining normal function of the heart [105,106], including excitation spread and coordinated contractility.…”
Section: Mechanisms Of Spatially Discordant Alternansmentioning
confidence: 99%
“…However, the mechanisms underlying these ECG indices, and their relationship to lethal arrhythmias, are not fully understood. Computational models of the heart have made inroads in this clinical cardiology arena [17,18,38,47,66,85,90,137]. Specifically, research has reported a strong correlation between increased arrhythmia risk and the presence of microvolt T-wave alternans (MTWA) [26,58].…”
Section: Modeling To Identify Individuals With a High Risk Of Developmentioning
confidence: 99%
“…However, the mechanistic basis of MTWA preceding lethal ventricular arrhythmias has been under debate since MTWA is most successful in stratifying risk in patients at heart rates < 110 bpm, where APD restitution is flat [86]. Computational models of the left ventricular (LV) wall in combination with clinical data revealed that abnormal intracellular calcium handling underlies alternans in action potential voltage, which result in MTWA at heart rates < 110 bpm [17,85]; abnormalities in intracellular calcium have long been linked to ventricular fibrillation [80,129]. Computational modeling studies have also shown that under conditions of abnormal calcium dynamics, the T-wave alternans magnitude is enhanced by structural heterogeneities in the myocardium [47].…”
Section: Modeling To Identify Individuals With a High Risk Of Developmentioning
confidence: 99%